Selection and characterisation of FVIII-specific single chain variable fragments - Naumann, A.; Scherger, A. K.; Neuwirth, J.; Orlowski, A.; Kahle, J.; Schwabe, D.; Königs, C. (Hämostaseologie, 2013)
The development of inhibitory anti-FVIII antibodies is currently the most severe complication in the treatment of haemophilia A patients. Inhibitor eradication can be achieved by immune tolerance induction (ITI). Recent findings suggest a correlation between the FVIII-specific IgG subclass distribution and the duration or outcome of ITI. To quantify FVIII-specific IgG subclasses in patients’ plasma FVIII-specific IgG standards are required. Here, the isolation of FVIII-specific single chain variable fragments (scFvs) from synthetic phage display libraries and the characterisation of their FVIII domain specificity are described. The isolated scFv 1G10, which binds to the FVIII A2 domain, was cloned into the context of the four human IgG (hIgG) subclasses and expressed in mammalian cells. Purified 1G10-hIgG1, -hIgG2, -hIgG3 and -hIgG4 are used as standards to determine the absolute amounts and relative contribution of the different FVIII-specific IgG subclasses in future studies. The results from these studies will eventually add to understanding the role of the FVIII-specific IgG subclass distribution as prognostic factor for the outcome of ITI.
Keywords: Haemophilia A; phage display; FVIII inhibitors; IgG subclasses